The impact of branding towards cosmetics products: a comparison study between generation Y and generation Z - Lee, Clement Jian Beng; Lam, Jeen Mun; Ng, Sut Kian; Ooi, Shi Ying; Tai, Yu Shiuan (2019)
The impact of branding towards consumer behaviour. A comparison study between generation Y and generation Z in Perak state. This research aim to examine the relationship between brand loyalty, brand awareness, brand credibility, brand congruence and brand image which have a significance over the dependant variable which is consumer behaviour. This research will be conducted using quantitative research method, whereby questionnaire will be distributed to targeted audiences for testing numerous hypothesis. The data will be analysed by using Statistical Package for the Social Science (SPSS). The respondent for this research is citizen of Perak state between generation Y and generation Z that uses cosmetic brand, they will be distributed with the survey questions to run the data for this research. The sampling method that will be used is probability sampling, proportionate stratified random sampling. On the other hand, the finding of this research will be able to prove that branding of cosmetic products may or may not have an impact on consumer behaviours. Based on the results, it may prove that independent variables used has significant connection with consumer behaviour. In our modern society, many cosmetic brand focus on branding in order to grab more audience. Brand owners should invest more towards their branding based on the variables above. This research may help advertisers to understand more about their audience. Other than that, brand owners should invests into their branding as it will achieve a stronger perception regarding their products. Furthermore, it would also provide information regarding the consumer behaviour toward their brand which would help them improved in multiple sectors.